(3GdEHJgGL TQM GdefgGL ddfhhis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3Ghd cJGH GdbQGV s
(3BNQgG (B:s
(3BNQ cJGH GdLeGdI s
(3ef GdfSNI GdSGHbIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B285 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1873s
Keywords: (3Gdabg GdTGaYjs